Optimization of low-cost drying methods and kinetics of degradation of gamma-linolenic acid in spirulina during accelerated storage test - Tiburcio, Perlita C. (2002)
Three relatively inexpensive drying methods were optimized to produce dried Spirulina of optimum quality at minimum cost. Quality was evaluated in terms of the product's oxidative stability. Oxidative stability of the samples during pretreatment and drying was measured using the thiobarbituric acid (TBA) test. Gamma linolenic acid (GLA) degradation during temperature-accelerated storage test was monitored using gas chromatography (Le Page Method). Of the two oxidants used in the pretreatment stage, tertiarybutylhydroquinone (TBHQ) was found to be better than α-tocopherol in minimizing lipid peroxidation. Between the two blanching methods used in inactivating enzymes, microwave blanching exerted a greater stabilizing effect than convective heat blanching. Among the three inexpensive drying methods optimized, sun drying produced a dried product whose oxidative stability measured as thiobarbituric acid reactive substances (TBARS=0.472) was nearest the spray dried (control) sample (0.434). GLA degradation in Spirulina followed first-order (n=1) reaction kinetics. The degradation rate constants (kr) of GLA obtained at a temperature range of 45-55°C were 4.0^-2 to 8.8^-2 day^-1. The energy of activation (Ea) obtained at the same temperature range was 16.53 kcal/mol. The computed Q10 was 2.22. The predicted shelf life of dried Spirulina at 30°C using the Arrhenius plot based on 20 percent GLA degradation is 263 days or 8.6 months and 258 days or 8.5 months in the Q10 approach.